Economic Importance of the Organization of the Transport Logistics System (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2023)
The article examines the impact on the efficiency of industrial production at all links of the supply chain, considers issues of increasing and reducing costs, in particular issues related to important elements of product distribution, such as procurement, storage, packaging. and vehicles were taken into account. The problems faced by logistics companies are analyzed. The advantages and disadvantages of technologies being introduced into logistics are identified, and proposals are made to improve the efficiency of their use.